ANALISIS KEBUTUHAN PENYARINGAN UDARA UNTUK MENGATASI POLUSI UDARA SEBAGAI STRATEGI AKUPUNKTUR KOTA DI KAWASAN INDUSTRI PULOGADUNG - Stefanie Fedora; Priscilla Epifania Ariaji (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Industrial area is one of the sources of air pollution in the city of Jakarta. Poor air quality has a negative impact on public health. Air filtration technology can be used as a solution to deal with air pollution problems around industrial areas. Air filtration technology Combined Flue Gas Cleaning (FGC) system is a way to overcome air pollution problems by analyzing the needs of air filtration in the Pulogadung Industrial Estate. Based on the application of air filtering technology and an analysis of the need for filtering technology, it can certainly provide a solution in the form of suppressing the amount of air pollution resulting from industrial activities, which will also have implications for improving air quality in the city of Jakarta. In addition, it also aims to inspire other industrial areas by implementing the Combined Flue Gas Cleaning (FGC) air filtration technology system. The green architectural approach in this design is carried out through the use of green materials as an instrument for reducing emissions in industrial areas. This study uses the literature method and secondary data analysis methods by zoning the Pulogadung Industrial Estate, and using the shape grammar design method. The combination of the results of the analysis produces urban acupuncture points in the Pulogadung Industrial Estate, with a radius and capacity that can be reached by the Combined Flue Gas Cleaning (FGC) air filtering technology, so that the connection between air filtration technology and urban acupuncture works in the Pulogadung Industrial Estate. Keywords: Green Architecture; Industrial Estate Pollution; Pollution Filtration; Urban Acupuncture Abstrak Kawasan industri merupakan salah satu sumber polusi udara di Kota Jakarta. Buruknya kualitas udara memberikan dampak yang negatif  bagi kesehatan masyarakat. Teknologi penyaringan udara dapat dijadikan sebagai solusi untuk menangani permasalahan polusi udara di sekitar kawasan industri. Teknologi penyaringan udara Combined Flue Gas Cleaning (FGC) sistem merupakan cara untuk menanggulangi permasalahan polusi udara dengan melakukan analisis kebutuhan penyaringan udara di Kawasan Industri Pulogadung. Berdasarkan penerapan teknologi penyaringan udara tersebut serta adanya analisis kebutuhan teknologi penyaringan tentunya dapat memberikan solusi berupa penekanan jumlah polusi udara hasil aktivitas industri, yang juga akan berimplikasi pada peningkatan kualitas udara di Kota Jakarta. Selain itu, juga bertujuan untuk menginspirasi kawasan industri lainnya dengan menerapkan sistem teknologi penyaringan udara Combined Flue Gas Cleaning (FGC). Pendekatan arsitektur hijau pada perancangan ini dilakukan melalui penggunaan material hijau sebagai instrumen penekan emisi di kawasan industri. Penelitian ini menggunakan metode literatur dan metode analisis data sekunder dengan menzoning Kawasan Industri Pulogadung, serta menggunakan metode perancangan shape grammar. Penggabungan hasil analisis menghasilkan titik-titik urban akupunktur pada Kawasan Industri Pulogadung, dengan radius dan kapasitas yang dapat dijangkau oleh teknologi penyaringan udara Combined Flue Gas Cleaning (FGC) tersebut, sehingga diperoleh keterhubungan antara teknologi penyaringan udara dengan urban akupunktur bekerja dalam Kawasan Industri Pulogadung.